Ephorus and Alexander the Great (FGrHist 70 F 223) - Yates, David C. (Histos, 2022)
Scholars have long maintained that Ephorus began work on the Histories in the middle years of the fourth century, and so place its genesis and most of its composition before the reign of Alexander the Great. A fragment that mentions Alexander’s crossing into Asia (FGrHist 70 F 223) has long been dismissed, but this article argues that it accurately reflects the content of the Histories and most likely appeared in Book 1, which suggests that Ephorus was composing this work decades later than generally thought, during the reign of Alexander.